2019
DOI: 10.51485/ajss.v4i2.86
|View full text |Cite
|
Sign up to set email alerts
|

Power Quality Detection, Classification and Monitoring Using LABVIEW

Abstract: In recent years, Power Quality becomes increasingly a major concern for both electric utilities and end users. Accordingly, the electrical engineering community has to deal with the analysis, diagnosis and solution of PQ issues using system approach rather than handling these issues as individual problems. This paper describes the analysis of PQ using advanced signal processing tools represented in Hilbert & Wavelet Transforms (HT-WT) and artificial intelligence tools represented in Artificial Neural Netwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 0 publications
0
4
0
3
Order By: Relevance
“…Under such a background, it is urgent to build a comprehensive evaluation index system and corresponding evaluation methods that can reflect the coordinated development (CD) of NE and regional power grids, so as to enhance the identification of the degree of development coordination between the two. e results of the study found the key influencing factors of the CD, and provided a reference for the relevant departments to formulate the promotion measures for the CD of the two [4]. In addition, there are still many problems in the current electricity market system, such as the competition mechanism only exists on the power generation side, and the electricity price mechanism cannot meet the market demand.…”
Section: Introductionmentioning
confidence: 91%
“…Under such a background, it is urgent to build a comprehensive evaluation index system and corresponding evaluation methods that can reflect the coordinated development (CD) of NE and regional power grids, so as to enhance the identification of the degree of development coordination between the two. e results of the study found the key influencing factors of the CD, and provided a reference for the relevant departments to formulate the promotion measures for the CD of the two [4]. In addition, there are still many problems in the current electricity market system, such as the competition mechanism only exists on the power generation side, and the electricity price mechanism cannot meet the market demand.…”
Section: Introductionmentioning
confidence: 91%
“…erefore, the problem of distribution network reconfiguration has also become the research focus of scholars at home and abroad. Literature [6] considered the randomness of wind power output, established a mathematical model with the goal of minimizing network loss and used Wasserstein distance to describe the similarity of wind power scenario models. Literature [7] considers the timing of the fan output and reduces the operating cost of the system through the dynamic reconfiguration strategy of the distribution network.…”
Section: Introductionmentioning
confidence: 99%
“…Velkovski ve Kokolanski, güç kalitesi bozulmalarının farklı türleri ve kombinasyonlarını çeşitli sürelerde üretme ve bunları donanım üzerinde yeniden üretebilme ve kaydetme yeteneğine sahip sistemi LabVIEW üzerinde geliştirmişlerdir [15]. Dekhandji ve arkadaşları, güç kalitesi bozulmalarının tespiti ve sınıflandırılması için Hilbert ve Dalgacık dönüşümleri ile gelişmiş sinyal işleme araçlarını ve Yapay Sinir Ağı ve Destek Vektör Makinesi gibi yapay zeka araçlarını kullanarak güç kalitesi analizini LabVIEW üzerinde gerçekleştirmişlerdir [16]. LabVIEW ile endüstriyel tüketici güç kalitesinin analizi için sanal enstrümantasyona dayalı bir sistem tasarlayarak 3 faz gerilim ve akım verilerini ve güç parametrelerini toplayan ve hesaplayan izleme aracı geliştirmişlerdir [17].…”
Section: şEkil 1 Labview Ortamında Sunulan Hazır Bileşenlerunclassified
“…Güç sistemlerinde belirli seviyelerde gürültü bulunur. Bir güç sistemindeki kabul edilebilir gürültü nominal genlik değerinin yaklaşık %0,7 ila %0,9 oranında genlikte olup 50 dB ila 48 dB arasındadır [16]. Gürültü bozulmaların tespitinde başarıma etki eden önemli parametrelerden bir tanesidir.…”
Section: A Güç Kalitesi Olay İşaretlerinin üRetilmesiunclassified